The effect of feeding soy waste on growth performance and crude protein composition in red hybrid tilapia - Mohd Joha, Muhammad Haziq (2016)
One of the commonest interests in tilapia farming worldwide is to diminish production cost particularly on the feeding cost and extends outputs in the shortest time. Soy waste is one of the locally available waste products which have high protein content and has potential to be used as one of the feedstuffs in animal feed. Hence, this study was aimed to determine the effect of feeding soy waste on growth performance and crude protein composition in Red Hybrid Tilapia. Forty-five juvenile Red Hybrid Tilapia was divided into 3 groups (Group 1: 40% soy waste + 60% commercial diets; Group 2: 20% soy waste + 80% commercial diets; and Group 3: control, no inclusion of soy waste). Proximate analysis on formulated diet was done and it shows that protein content higher as the inclusion of soy waste increasing in the diet. Result shows that the inclusion of soy waste into commercial diet is significant in group with highest soy waste percentage as compared to control group in relation to its body weight, length, girth and the fish protein composition. Indeed, Group 1, which has 40% inclusion of soy waste contain high protein and fat as compared to other groups. Thus, the fish from group 1 is more likely to have better growth performance and protein composition.